IMPLEMENTASI KEARIFAN LOKAL MELALUI MODEL BCCT UNTUK PENGEMBANGAN KEMAMPUAN SOSIAL ANAK USIA DINI - Dian Wahyuningsih; Slamet Suyanto (Universitas Negeri Yogyakarta, 2015)
This study aims to reveal the social development of early childhood through the implemen-tation of local wisdom embodid in the play of children through the BCCT model. This research was a descriptive qualitative research with a phenomenology approach by describing each pheno-menon which appears in the field. The subjects in this study were children's developments of the age of 5-6 years. The technique of data analysis was the inductive model of Creswell. The results shows that the values of local wisdom introduced to children include: (1) to be grateful, to be happy, to be always happy, to not be arrogant, to not be stubborn, to be confident, to make other people happy, to do the tasks and responsibilities as humans, to show togetherness, to think critically, to be careful, to be sincere (legowo), to keep good relation (silaturahmi), to respect events in the past, to be patient, to be meticulous, to be creative, to respect local are products and to maintain good etiquettes (unggah-ungguh); (2) The values of local implemented through traditional songs, traditional games, historical places and the surroundings, traditional food, clothing, as well as the Javanesse; (3) The social development of the child are cooperative, tolerance, empathy, understanding the environment, understanding oneself, and friendship in the play activities of children continued to increase in in four months during the research; (4) there are changes in the social behaviors of the children, which are from the stage of associative play to the stage of cooperative play shown in the activities including preparation, blocks, natural materials, socio drama, sand-water and exploration; (5) the integration process of local wisdom values with BCCT and social development in the process of playing can instill positive characters since young. Thus, kindergarten can use the values of local wisdom to develop social skills in early childhood through a special designed of BCCT.